2019
DOI: 10.5296/ijsw.v6i2.15567
|View full text |Cite
|
Sign up to set email alerts
|

The Current Practice of Corporate Social Responsibility in Ethiopia

Abstract: The responsibility of the organization for the impacts of its decisions and activities on the society and the environment, called Corporate Social Responsibility is evolving investment approach aimed mainly to contribute for sustainable development and welfare of the society. CSR is being integrated with economic and investment policy of different countries and practiced in different modalities. In Ethiopia, literatures indicates that only limited local as well as international or multinational organizations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Firms are challenged to implement pollution controls and other environmentally friendly initiatives. If these issues are unresolved, it forms risk depleting resources and harming society by concentrating only on their economic interests (Tilaye, 2019). Recently, researches on CSR and business achievement confirmed that, CSR significantly increase economic performance (Hernández et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firms are challenged to implement pollution controls and other environmentally friendly initiatives. If these issues are unresolved, it forms risk depleting resources and harming society by concentrating only on their economic interests (Tilaye, 2019). Recently, researches on CSR and business achievement confirmed that, CSR significantly increase economic performance (Hernández et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, in Ethiopia, there is no comprehensive CSR guideline, policy, or a legal document (Demamu, Alemayehu, 2020). It appears fragmented, embedded in, and with different legal infrastructures (Tilaye, 2019).…”
Section: Business Management and Strategymentioning
confidence: 99%
“…According to the interpretations, the term social refers to a company's obligation towards the public. For the success of business institutions, being socially responsible can maximize the positive effects and reduce the adverse impact on society (customers, owners, employees, suppliers, community, and government) [49]. For this study, CSR practice is defined as working on community development such as infrastructure expansion like health center buildings, road construction, school building, and pure water supply.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%